Surgical Management of Brain Abscess in Bauchi, Nigeria: A Single-Center Study - Ogunleye, Olabisi O.; Muhammad, Abubakar S.; Amur, Ibrahim; Ogunleye, Oluchukwu B. (Nigerian Journal of Basic and Clinical Sciences, 2024)
ContextBrain abscess is an area of focal intracranial infection, which begins with cerebritis and later becomes capsular stage with surrounding vascularization. The route of transmission is mainly through contiguous structures, hematogenous spread, and complication of traumatic brain injury. Brain abscess continues to pose great challenges in diagnosis and treatment in both developed and developing countries. We investigated the demography, clinical presentations, laboratory, and factors associated with the outcomes.AimsTo review the patients with brain abscess that were managed in our hospital and to determine the factors that predict the outcomes.Setting and DesignRetrospective cross-sectional design.MethodologyWe conducted a study on twenty-nine patients who had surgical treatment for intracerebral brain abscess in our facility between September 2018 and September 2022. Demography, clinical features, laboratory findings, and outcomes of the patients were analyzed.Statistical Analysis UsedCategorical data were analyzed with the Chi-square, and multivariate regression analysis was performed to identify predictive factors for the outcomes of the patients.ResultsTwenty-nine patients had surgical drainage of intracerebral abscess in various locations. Male-to-female ratio is of 2.2:1. Most intracranial abscesses that had surgical intervention occurred in the 2nd and 4th decade of life, with each accounting for 31%. The predisposing factors were mainly chronic otitis media (28%), chronic sinusitis (14%), post-meningitis (24%), and post-TBI (17%).All the patients had headache, and only 24% of them had seizure at presentation. Positive bacterial culture was seen in 31% of the patients. Sex and the presence of headache were independently associated with poor outcome with P value of 0.005 and 0.033, respectively.ConclusionPrevention, early diagnosis, and treatment are key to improving prognosis. Most of our patients had good outcome. However, sex and headache as factors are poor predictors of poor prognosis.
Keywords: Brain abscess; outcomes; predictors; risk factors